That's my story, and I'm sticking to it—an update on B. burgdorferi adhesins - Brissette, Catherine A.; Gaultney, Robert A. (Frontiers in Cellular and Infection Microbiology, 2014)
Adhesion is the initial event in the establishment of any infection. Borrelia burgdorferi, the etiological agent of Lyme disease, possesses myriad proteins termed adhesins that facilitate contact with its vertebrate hosts. B. burgdorferi adheres to host tissues through interactions with host cells and extracellular matrix, as well as other molecules present in serum and extracellular fluids. These interactions, both general and specific, are critical in the establishment of infection. Modulation of borrelial adhesion to host tissues affects the microorganisms ’s ability to colonize, disseminate, and persist. In this review, we update the current knowledge on structure, function, and role in pathogenesis of these “sticky” B. burgdorferi infection-associated proteins.